2006
DOI: 10.2353/ajpath.2006.050876
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Enhances the Oncogenic Potential of Human Thyroid Carcinoma Cells

Abstract: The role of members of the insulin-like superfamily in human thyroid carcinoma is primarily unknown. Here we demonstrate the presence of RLN2 relaxin and relaxin receptor LGR7 in human papillary, follicular, and undifferentiated anaplastic thyroid carcinoma suggesting a specific involvement of relaxin-LGR7 signaling in thyroid carcinoma. Stable transfectants of the LGR7-positive human follicular thyroid carcinoma cell lines FTC-133 and FTC-238 that secrete bioactive proRLN2 revealed this hormone to act as a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 58 publications
8
103
0
Order By: Relevance
“…Relaxin (RLN2) confers increased carcinoma cell motility and in vitro invasiveness in human thyroid carcinoma cells and this process is mediated by the relaxin receptor, relaxin family peptide receptor 1 (RXFP1; ref. 10). Furthermore, we showed that in human thyroid carcinoma cells, the enhanced migration through elastin matrices was mediated as a result of relaxin-induced increase in the production and secretion of elastinolytic cathepsin-L (10).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Relaxin (RLN2) confers increased carcinoma cell motility and in vitro invasiveness in human thyroid carcinoma cells and this process is mediated by the relaxin receptor, relaxin family peptide receptor 1 (RXFP1; ref. 10). Furthermore, we showed that in human thyroid carcinoma cells, the enhanced migration through elastin matrices was mediated as a result of relaxin-induced increase in the production and secretion of elastinolytic cathepsin-L (10).…”
Section: Introductionmentioning
confidence: 83%
“…10). Furthermore, we showed that in human thyroid carcinoma cells, the enhanced migration through elastin matrices was mediated as a result of relaxin-induced increase in the production and secretion of elastinolytic cathepsin-L (10).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…CTRP8‐activated RXFP1 may utilize PI3K to mediate STAT3 activation as PI3K and its target BMX TEC kinase were recently shown to mediate the phosphorylation of STAT3 (Glogowska et al ., 2013; Hart et al ., 2011). We also previously identified lysosomal cathepsins as targets of H2 relaxin, the cognate ligand of RXFP1, and CTRP8 in human thyroid cancer (cathepsin‐D and cathepsin‐L) and GBM (cathepsin‐B), respectively (Glogowska et al ., 2013; Hombach‐Klonisch et al ., 2006). High cathepsin‐B serum levels are associated with poor prognosis in GBM patients (Strojnik et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%